2019
DOI: 10.3390/cells8101135
|View full text |Cite
|
Sign up to set email alerts
|

MiR-20b Down-Regulates Intestinal Ferroportin Expression In Vitro and In Vivo

Abstract: Ferroportin (FPN) is the only known cellular iron exporter in mammalian. However, post-transcriptional regulation of intestinal FPN has not yet been completely understood. In this study, bioinformatics algorithms (TargetScan, PicTar, PITA, and miRanda) were applied to predict, screen and obtain microRNA-17 family members (miR-17, miR-20a, miR-20b, and miR-106a) targeting FPN, ‘seed sequence’ and responding binding sites on the 3′untranslated region (3′UTR) region of FPN. Dual-luciferase reporter assays reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…There is evidence that microRNAs such as miR-485-3p, miR-20a and miR-20b, can posttranscriptionally downregulate ferroportin but the physiological role of this mechanism is uncertain [ 37 , 39 , 40 ].…”
Section: Regulation Of Ferroportin By Intracellular Signalsmentioning
confidence: 99%
“…There is evidence that microRNAs such as miR-485-3p, miR-20a and miR-20b, can posttranscriptionally downregulate ferroportin but the physiological role of this mechanism is uncertain [ 37 , 39 , 40 ].…”
Section: Regulation Of Ferroportin By Intracellular Signalsmentioning
confidence: 99%
“…Decreasing miR-148a expression induced high expression of TFR1, resulting in increased cellular iron and cell proliferation in hepatocellular carcinoma [63]. Two other miRNAs, miR-20a and miR-20b, suppress FPN expression in lung cancer and intestinal cells, regulating intracellular iron export [35,64]. The present results indicated that the expression of the hepatic miR-181 family members was significantly impaired in chronic variable stress-loaded rats.…”
Section: Discussionmentioning
confidence: 54%
“…2.11. Quantification of miRNA with Real-Time PCR Analysis of miRNA was conducted according to previous descriptions [31,35]. After treating with RNase-free DNase I (2270A, Takara, Otsu, Japan), total RNA (6 µg) was polyadenylated at 37 • C for 1 h using Poly (A) Tailing Kit (AM1350, Applied Biosystems, Waltham, MA, USA), then reverse transcribed for use in qPCR.…”
Section: Prediction Of Mirna Targeting Zip14mentioning
confidence: 99%
“…Based on the miRNA sequencing results, upregulated miRNAs of mature sequences from Rattus norvegicus were retrieved from the miRBase ( , October 2018) and applied to predict the binding capability of the target gene (FASN or FABP1) through complementary base pairing. The target miRNAs were verified in vivo using the miRNA reverse transcription kit and quantification kit (Hongsheng, Nanjing, China), as reported previously [ 36 ]. The sequences of all primers are listed in Table S3 .…”
Section: Methodsmentioning
confidence: 99%